Using Rasch measurement to improve analytical marking keys - Tarricone, P.; Cooper, Martin (NZCER Press, 2014)
This article describes the use of Rasch measurement to improve criteria-based analytical marking keys. The instruments and data described result from a research project which investigated the use and assessment of digital portfolios in the Western Australian senior secondary design course. The study involved two phases and two separate data sets. A criteria-based analytical marking key was used to score the portfolios in Phase 1, and a refined and improved version was used in Phase 2. Refinement of the criteria-based analytical marking key was undertaken as a result of Rasch analysis, and this is described and illustrated. Results showed that Rasch measurement can inform the improvement of marking keys in terms of criteria, targeting, number of score points, utilisation of score points, and item discrimination.